Uma nova face da imigração: um estudo dos expatriados sul coreanos e sua inserção social em São Paulo - Bae, Ester (2019)
This dissertation has the objective of studying and identifying some perspectives of the concrete reality of young expatriates in São Paulo, with the purpose of analyzing the socialization of expats in the city of São Paulo. In order to do so, the group of South Korean executives was sought in the age group between 20 and 40 years old, shedding light on common characteristics in the trajectory of expatriates who immigrated on account of work, and the insertion of these in São Paulo in the reflection of sociability of the expatriates in an increasingly globalized and modern world. To make the appreciation of these, the 12 South Korean executives, 4 executive wives and 6 expatriates of Dutch, French, Indian, Japanese, Filipino and Chinese origin were taken as the center of analysis. In addition to the interviews, a bibliographical, documentary, news, and numerical data survey of the theoretical framework on the themes involved was made through the reflections on the alterity and identity of the authors of varied areas and origins, of which the focus was directed to those of Arjun Appadurai, Saskia Sassen, Georg Simmel, Clifford Geertz, Luc Boltanski, Stuart Hall and Oswaldo Truzzi, from which quantitative and qualitative information was produced